PERUBAHAN FRASA PUTUSAN OLEH HAKIM MAHKAMAH KONSTITUSI SAAT SIDANG PENGUCAPAN PUTUSAN (STUDI PUTUSAN MAHKAMAH KONSTITUSI NOMOR 103/PUU-XX/2022): Changes in Decision Phrases by Constitutional Court Judges During the Decision Pronouncement Session - Lie, Ribka Yonathan; Pamungkas, Yogo (AMICUS CURIAE, 2024)
The Judges' Deliberative Meeting (RPH) is a plenary meeting which is held behind closed doors and is confidential with the aim of discussing a case, making a decision and determining a verdict. With the existence of a Judges' Deliberative Meeting (RPH), this will make it easier for Constitutional Justices to give opinions on submitted applications and draft decisions before they are pronounced in a decision-making hearing open to the public. The formulation of the problem in this journal is whether the change in the phrase of the decision by the Constitutional Judge at the time of pronouncing the decision is in accordance with Law Number 24 of 2003 concerning the Constitutional Court and what are the legal consequences of the change of phrase in decision Number 103/PUU-XX/2022 during the hearing decision by a Constitutional Court Judge. The type of legal research used in this research is normative legal research using secondary and primary data, analyzed qualitatively and conclusions drawn deductively. The results of this research are the change in the phrase "Therefore" to "In the future" in decision no. 103/PUU-XX/2022 is not in accordance with Article 45 paragraph (4) to paragraph (10) of Law no. 24 of 2003 concerning the Constitutional Court and has not implemented the Standard Operating Procedure (SOP) and mechanisms as the Constitutional Court decision should be read and uploaded. This means that there was an administrative error in the process of uploading the decision text to a page that can be accessed by the public and as a result of the change in the phrase of decision No. 103/PUU-XX/2022 during the announcement hearing by the Constitutional Court judges was that because the change was substantive in nature it would give rise to a different meaning and the decision that was uploaded due to an administrative error also had legal consequences for public reports and the Honorary Council's examination. Apart from that, the actions carried out by the reported judge violated the Sapta Karsa Hutama or what is usually called the Code of Ethics and Behavior of Constitutional Judges.